2010
DOI: 10.1080/00071668.2010.518408
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of chickenMC1Rgene in different plumage colour populations

Abstract: 1. Genetic variation in the chicken MC1R gene was analysed through bioinformatic methods after polymerase chain reaction (PCR) amplification and sequencing of the coding region of MC1R gene from 5 different populations with 4 plumage colours (black, grey plumage with black spots, yellow plumage with black spots, red). 2. A total of 11 novel variations were detected in Hebei chickens, of which 8 were non-synonymous. Allele distribution analysis showed that the wild-type e(+) (Brown Leghorn) allele was mainly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…Therefore, it is suggested that, at least in ducks, the two missense SNPs, c.52A>G and c.376 A>G (p.Lys18Glu and p.Ile126Val respectively), may have a major effect on the extended black phenotypes. Additionally, the p.Val126Ile substitution in the third transmembrane domain of MC1R is associated with plumage pigmentation in chicken and duck (Kerje et al, 2003;Guo et al, 2010;Yu et al, 2012;Oh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that, at least in ducks, the two missense SNPs, c.52A>G and c.376 A>G (p.Lys18Glu and p.Ile126Val respectively), may have a major effect on the extended black phenotypes. Additionally, the p.Val126Ile substitution in the third transmembrane domain of MC1R is associated with plumage pigmentation in chicken and duck (Kerje et al, 2003;Guo et al, 2010;Yu et al, 2012;Oh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A retroviral insertion in the TYR (tyrosinase) gene is associated with a recessive white mutation in chickens [10]. MC1R genes play a role in the rich diversity of plumage colour in chickens [12, 13]. Avian plumage colour is a complex trait involving major functional genes.…”
Section: Introductionmentioning
confidence: 99%
“…The highly significant nonsynonymous mutations (Met71Thr, Glu92Lys, Ala126Ile, Thr143Ala, Cys213Arg and His215Pro) were associated with eumelanin and pheomelanin in chicken plumage colors (Guo et al, 2010;Kerje et al, 2003). Study in chicken breed discrimination has extended exiting knowledge on plumage color controlled by the MC1R gene locus might be a candidate marker.…”
Section: Mc1r Genementioning
confidence: 99%
“…The LEI0258 allele sizes with those repeat and polymorphic structure shared among several distinct B haplotypes which completely sequence the LEI0258 locus in Korean native chicken compared with genetic resources (Table 2). Nonsynonymous Kerje et al, 2003;Guo et al, 2010;Tixier-Biochard, 2011 These sequence data revealed distinguishing SNP differences for some of these haplotypes. Despite the many generation of separation, the allelic identity is carried by the sequence information.…”
Section: Lei0258 Markermentioning
confidence: 99%
See 1 more Smart Citation